Links Between Arts and Health, Examples From Quantitative Intervention Evaluations - Theorell, Töres (Frontiers in Psychology, 2021)
Statistical evaluations of the effects of arts interventions on health have been relatively uncommon. Until recently it has been difficult to find funding for this kind of research. The author presents eight projects which have been executed and published despite small financial resources from our group of researchers since the early 1980:s. In these examples, statistical methods with longitudinal designs and mostly control groups have been used. Some of them are random control trials. Physiological and endocrinological variables have been assessed in some of these studies in efforts to increase our understanding of how music experiences and other kinds of arts experiences interact with bodily reactions of relevance for health development. Although some of these projects have suffered from low statistical power and other methodological weaknesses they show that it is possible to do statistical evaluations of arts interventions aiming at improved health. Although this is not specifically addressed in this contribution, qualitative evaluations have also been performed in the projects.